Work Ability and Quality of Life in Metal Industry Workers: A Cross-Sectional Study - Yasser Labbafinejad; Sepideh Lamei Haghighat; Tahereh Babajani Roshan; Omid Asghari; Negin Kassiri (Journal of Cardio-Thoracic Medicine)
Introduction: Cardiovascular diseases are one of the leading causes of mortality and disability, as well as a major public health burden worldwide.Methods: This study is a cross-sectional, descriptive-analytical study conducted in 2023 on all workers of a metal industry factory. The inclusion criteria for the study were a work history of over one year and an age above 40 years. Exclusion criteria included unwillingness to participate and a diagnosed history of coronary disease, stroke, or transient ischemic attack. The quality of life (QoL) of the participants was assessed using the SF-12 Quality of Life Questionnaire, the Work Ability Index was measured through the Work Ability Index questionnaire, and the ten-year cardiovascular disease risk was determined using the WHO/ISH chart. Finally, the relationship between the QoL and work ability indices with the ten-year cardiovascular risk was examined.Results: A survey of 187 employees in a metal industry revealed a significant relationship between the QoL index and job title (p value: 0.001) as well as smoking history (p value: 0.024). Regarding the work ability index, significant relationships were found with variables such as job type (p value: 0.000), education (p value: 0.000), physical activity (p value: 0.006), age (p value: 0.023), work history (p value: 0.000), and ten-year cardiovascular risk (p value: 0.003). In linear regression analysis, physical activity and work history showed a significant relationship with the work ability index, while job type remained significantly associated with quality of life (p value<0.05).Conclusion: The results of our study demonstrate a significant relationship between job type and QoL, as well as physical activity and work history with the work ability index. Individuals with less work history and those engaging in regular physical activity reported a higher work ability index. Production workers, assemblers, and welders had a lower quality of life compared to warehouse workers and forklift drivers